2021
DOI: 10.1021/acssynbio.1c00430
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Cell-Free Replication and Evolution of Artificial Genomic DNA in a Compartmentalized Gene Expression System

Abstract: In all living organisms, genomic DNA continuously replicates by the proteins encoded in itself and undergoes evolution through many generations of replication. This continuous replication coupled with gene expression and the resultant evolution are fundamental functions of living things, but they have not previously been reconstituted in cell-free systems. In this study, we combined an artificial DNA replication scheme with a reconstituted gene expression system and microcompartmentalization to realize these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 57 publications
0
44
0
Order By: Relevance
“…Recently, we found that the replication efficiency of circular DNA spontaneously improves through long-term replication due to Darwinian evolution. 18 A similar long-term replication would allow the evolution of highly replicable template DNA encoding tRNA. Another advantage of in vitro evolution is the improvement of tRNA sequences.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we found that the replication efficiency of circular DNA spontaneously improves through long-term replication due to Darwinian evolution. 18 A similar long-term replication would allow the evolution of highly replicable template DNA encoding tRNA. Another advantage of in vitro evolution is the improvement of tRNA sequences.…”
Section: ■ Discussionmentioning
confidence: 99%
“…All components of the laboratory-made PURE system were prepared as previously described. 18 EF-Tu was purified using a nickel column. For EF-Tu repurification, purified EF-Tu was 10-fold diluted with a stringent buffer [50 mM HEPES−KOH (pH 7.6), 1 M KCl, 10 mM MgCl 2 , 15% glycerol, 1 mM DTT, and 1% Triton X-100] and allowed to stand on ice for 1 h. The solution was injected into to the HisTrap column (Thermo Fisher Scientific) and washed with the same buffer, omitting Triton X-100.…”
Section: ■ Discussionmentioning
confidence: 99%
“…To face the difficulty of achieving high degrees of integration, an evolutionary approach has been proposed (Abil and Danelon, 2020). Directed evolution strategies should be considered as well (Sakatani et al, 2018;Okauchi and Ichihashi, 2021), especially when connected to adaptive responses. From the architectural viewpoint, complexification can be achieved via multiple compartmentalization.…”
Section: The Theoretical Track: What Scs Actually Arementioning
confidence: 99%
“…However, protein expression levels were low, which was not surprising as cell-free reactions require very high quantities of template DNA for efficient protein production [ 24 , 25 ]. The most obvious solution to this problem, namely the amplification of single DNA molecules directly within a transcription-translation droplet, turned out to be surprisingly difficult as reaction chemistries and temperatures are not entirely compatible [ 26 28 ]. The current work-around is a two-step approach consisting of in-droplet Polymerase Chain Reaction, followed by micro-injection or droplet merging into separately prepared cell-free droplets [ 29 32 ].…”
Section: Introductionmentioning
confidence: 99%